Utilization of Synthetic Calcium‐Phyllosilicates as Bifunctional Bases in the Matsuda‐Heck Reaction. Issue 2 (10th December 2018) - Brunner, Heiko; Vedder, Lennart
Abstract: Calcium‐phyllosilicates can successfully be used as novel bases in the Matsuda‐Heck reaction using methanol as solvent. The new experimental set‐up distinguishes itself by higher reactivity and better selectivity compared to other systems. Abstract : All your base are belong to us : Calcium‐phyllosilicates can successfully be used as novel bifunctional bases in the Matsuda‐Heck‐reaction using methanol as solvent. The new experimental set‐up distinguishes itself by higher reactivity and better selectivity compared to other systems.